2020
DOI: 10.1002/ana.25744
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Interictal Spikes during Sleep Impact Long‐Term Memory Consolidation

Abstract: Objective: Non-rapid eye movement (NREM) sleep is supposed to play a key role in long-term memory consolidation transferring information from hippocampus to neocortex. However, sleep also activates epileptic activities in medial temporal regions. This study investigated whether interictal hippocampal spikes during sleep would impair long-term memory consolidation. Method: We prospectively measured visual and verbal memory performance in 20 patients with epilepsy investigated with stereoelectroencephalography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…The use of memory paradigms combined with properly designed electrophysiological study (e.g., CCEPs, single unit recordings) could powerfully increase our knowledge of this critical brain function. Recent work with human and non-human primates, for example, is exploring the relationship between the electrophysiology of sleep (e.g., occurrence of sleep spindles) to memory consolidation processes (200)(201)(202). Of note, standard clinical neuropsychological batteries only assess patients after time spans under 1 h and never assess patients after periods of sleep (203).…”
Section: Learning and Memorymentioning
confidence: 99%
“…The use of memory paradigms combined with properly designed electrophysiological study (e.g., CCEPs, single unit recordings) could powerfully increase our knowledge of this critical brain function. Recent work with human and non-human primates, for example, is exploring the relationship between the electrophysiology of sleep (e.g., occurrence of sleep spindles) to memory consolidation processes (200)(201)(202). Of note, standard clinical neuropsychological batteries only assess patients after time spans under 1 h and never assess patients after periods of sleep (203).…”
Section: Learning and Memorymentioning
confidence: 99%
“…Therefore, it is currently believed that impaired memory consolidation caused by Hippocampal dysfunction might produce accelerated long-term forgetting. For example, a recent study has shown that both seizures and interictal spikes in hippocampus during sleep impair long-term memory consolidation, supporting the notion that hippocampal dysfunction causes accelerated long-term forgetting [26] .…”
Section: Discussionmentioning
confidence: 78%
“…IES in CECTS, due to their centrotemporal location and NREM occurrence, may perturb one or more of the oscillations within the hippocampal area as well as their neuronal coupling potentially leading to neurocognitive deficits. This is partially supported by the fact that in adults, hippocampal interictal spikes in NREM sleep negatively correlate with memory consolidation performance (Lambert et al, 2020).…”
Section: Interictal Epileptiform Spikes Issuesmentioning
confidence: 92%